Management of multiple pelvic organ prolapse due to pulmonary tuberculosis in a suburban hospital: A case report - Yurisqi Dian, S Yova; Toya Damara, Lazula; Talitha Raissa, D Diva; Olfah, Trimayanti; Santoso Putra, Galih (Indian Journal of Case Reports, 2024)
Pelvic organ prolapse (POP) is a condition in which the pelvic organs herniate into the vaginal canal or the vaginal introitus due to weakness of the pelvic floor support structures. The occurrence of POP is prevalent, especially in older women, with various other risk factors, including multiparity, obesity, menopause, malignancy, and chronic infections. We report a unique and rare case in which uterine prolapse was followed by cystocele and rectocele with the risk factors of advanced age, menopause, and chronic cough in a 73-year-old female who complained of a chronic cough for 2 months. When coughing, the patient experienced a protrusion coming out, especially from the vaginal canal. Other complaints included night sweats, urinary problems, and constipation. Additional sounds identical to fine rhonchi were found on auscultation examination in both lung fields. On examination of the external genitalia, a pink protrusion came out of the vaginal introitus, approximately the size of a chicken egg, accompanied by the hyperemic rectal mucosa protrusion through the anal canal. Chest X-ray results confirmed that there was an active tuberculosis infection.